1994
DOI: 10.1177/002076409404000306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Psychiatric Labels On Attitudes Toward Mental Illness in a Turkish Sample

Abstract: The influence of specific psychiatric labels and types of psychopathology on various attitudes were investigated in a sample (N = 84) of visitors of patients in a Turkish hospital. Vignettes representing two types of psychopathology with and without labels were used as the stimulus material and the attitudes toward those descriptions were assessed with the use of a questionnaire. Statistical analyses showed that labels had significant influence on recognition of mental illness, social distance, expected physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
25
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 27 publications
3
25
0
Order By: Relevance
“…Fears and/or distaste towards individuals with mental disorders are so powerful that just adding a diagnostic label to information related to a participant increases negative attitudes towards a hypothetical target relative to an identical target with no diagnostic label or a label that is not related to a psychiatric diagnosis (Arkar & Eker, 1994;Nieradzik & Cochrane, 1985). Although fears of individuals with mental illnesses are generally gross exaggerations of actual dangerousness, these fears can be challenging to alleviate (e.g., Penn & Link, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Fears and/or distaste towards individuals with mental disorders are so powerful that just adding a diagnostic label to information related to a participant increases negative attitudes towards a hypothetical target relative to an identical target with no diagnostic label or a label that is not related to a psychiatric diagnosis (Arkar & Eker, 1994;Nieradzik & Cochrane, 1985). Although fears of individuals with mental illnesses are generally gross exaggerations of actual dangerousness, these fears can be challenging to alleviate (e.g., Penn & Link, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Although healthcare professionals are expected to be more understanding and exhibit less stigmatizing attitudes towards mentally ill patients, the literature suggests otherwise. Healthcare professionals also exhibit negative attitudes towards mental illnesses such as schizophrenia, and these negative attitudes are exacerbated when mentally ill patients have been hospitalized in a secured setting.…”
Section: Introductionmentioning
confidence: 99%
“…Phillips (1966), for instance, cautioned that a distinction needs to be maintained between publically and psychiatrically defined mentally ill persons. Arkar and Eker (1994) emphasised the specificity of the influence of labels and they revealed significant effects of psychiatric labelling on some attitudes (namely, higher perception of mental illness, greater social distance, more expectation of physical burden, and a higher perception of treatment necessity), but no significant effects on other (expected emotional burden, expected influence on one's mental health, type of treatment, and prognosis).…”
mentioning
confidence: 99%
“…Apart from sample differences in terms of culture and demographic variables (Arkar & Eker, 1994), one important factor which has also been studied is that of the gender of the individual being judged. Broverman et al (1970), in a classic study, demonstrated that clinical judgments about the characteristics of healthy individuals differ as a function of the sex of the person judged.…”
mentioning
confidence: 99%